10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Despite the availability of preexposure prophylaxis (PrEP) and postexposure prophylaxis (PEP) for the prevention of HIV transmission, 30 000 new cases of HIV are reported every year in the United States. Barriers to PrEP and PEP use are multifactorial and include clinician misinformation, stigma, and varied access to ongoing training. To better understand the origin of these barriers, we reviewed recent Centers for Disease Control and Prevention (CDC) clinical guidelines for PrEP and PEP to identify changes, persistent gaps in guidelines, and opportunities for improvement. Our review found that not only do the updated PrEP guidelines still lack clarity on newer preventive medications and recommended screening schedules, but they also continue to rely heavily on risk-based screening frameworks that leave many eligible patients overlooked. Similarly, the PEP guidelines place substantial responsibility on patients to recognize their own exposure and seek treatment within a narrow initiation window, which may contribute to underuse of PEP. Based on these findings, we propose 4 key guideline recommendations: (1) update CDC guidance to clearly incorporate new PrEP and PEP regimens and prescribing practices, (2) emphasize annual screening for all sexually active patients rather than relying solely on risk-based criteria, (3) add PrEP/PEP-focused clinical guidance training in the didactic curriculum of medical and other health profession students, and (4) develop dedicated billing codes to support routine PEP screening and reduce administrative barriers for clinicians.